Kajian Hermeneutika Kontemporer: Studi Analisis atas Penafsiran Al-Qur’an Nasr Hamid Abu Zayd dan Hassan Hanafi - Muhammad Furqan; Sakdiah Sakdiah (TAFSE: Journal of Qur'anic Studies, 2022)
The term hermeneutics is still very unfamiliar to the majority of Indonesian Muslims, this is considered reasonable because hermeneutics is an imported item that is not known in Islam scientific world. In the Islamic world itself, although there was a lot of resistance to the results of its studies, it did not discourage some contemporary thinkers from adopting it and ignored the various risks it had to bear, such as Nasr Hamid Abu Zayd and Hassan Hanafi. This article aims to reconstruct their thinking on the interpretation of the Qur'an through the study of hermeneutics. This article is literature research using a qualitative approach. Data collection is carried out by studying related textbooks, encyclopedias, journals, and others. The results of the study showed that Nashr Hamid Abu Zaid tried to find a new meaning that was not pronounced in the Qur'an in accordance with the current context by carrying out hermeneutic studies through the theory of text interpretation in two dimensions, namely the theory of meaning (dalâlah) and significance (magzâ). Hassan Hanafi carries out the study of the hermeneutics of freedom with language analysis, historical context analysis and generalizations, that is, raising the meaning of the "moment" situation and its historical situation in order to give an adequate understanding of others' situation. Hanafi wanted to derive new meaning from interpretation to address specific cases in people's lives. Istilah hermeneutika masih sangat asing bagi mayoritas masyarakat Muslim Indonesia, hal ini dianggap wajar dikarnakan hermeneutika merupakan barang impor yang tidak dikenal dalam keilmuan Islam. Di dunia Islam sendiri, meski muncul banyak penolakan terhadap hasil pengkajiannya, namun tidak menyurutkan langkah sebagian pemikir kontemporer untuk mengadopsinya serta mengabaikan berbagai risiko yang harus ditanggungnya, Seperti Nasr Hamid Abu Zayd dan Hassan Hanafi. Artikel ini bertujuan merekonstruksikan pemikiran mereka terhadap penafsiran Al-Qur’an melalui kajian hermeneutika. Artikel ini merupakan penelitian kepustakaan dengan menggunakan pendekatan kualitatif. Pengumpulan data dilakukan dengan telaah buku-buku teks, ensiklopedi, jurnal, dan lainnya yang terkait. Hasil kajian menunjukkan bahwa Nashr Hamid Abu Zaid mencoba untuk menemukan makna baru yang tak terlafazkan dalam al-Qur’an sesuai dengan konteks kekinian dengan mengusung kajian hermeneutika melalui teori interpretasi teks dalam dua dimensi yaitu teori makna (dalâlah) dan signifikansi (magzâ). Hassan Hanafi mengusungkan kajian hermeneutika kebebasan dengan analisis bahasa, analisis konteks sejarah dan generalisasi, yaitu mengangkat makna dari situasi “saat” dan situasi sejarahnya agar dapat menimbulkan situasi-situasi lain. Hanafi ingin memperoleh makna baru dari penafsiran untuk menyikapi berbagai kasus spesifik dalam kehidupan masyarakat.